1967
DOI: 10.1136/bmj.1.5532.80
|View full text |Cite
|
Sign up to set email alerts
|

Conservative surgery for bleeding peptic ulcer.

Abstract: 1967, 1,[80][81][82] 3leeding peptic ulcer accounts for 80 to 85 ! ; ; of hospital admissions for gastrointestinal haemorrhage (Tanner, 1954 Avery Jones, 1957Aird, 1957). Improved supportive therapy and greater co-operation between physicians and surgeons have lowered the mortality in this condition. Mortality is influenced by the age of the patient, the severity of the bleeding, and the site of the ulcer. Patients over the age of 50 who continue to bleed may die unless treated surgically (Avery Jones, 1947).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

1968
1968
1973
1973

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…Until the aetiology and pathology of this condition are understood, and a complete and rational treatment has been worked out, it seems that operative treatment should be avoided because of its high mortality. Carruthers et al (1967) reported 13 cases of erosive gastritis treated by operation. Of four patients treated by gastrectomy one died after a further bleed.…”
Section: Discussionmentioning
confidence: 99%
“…Until the aetiology and pathology of this condition are understood, and a complete and rational treatment has been worked out, it seems that operative treatment should be avoided because of its high mortality. Carruthers et al (1967) reported 13 cases of erosive gastritis treated by operation. Of four patients treated by gastrectomy one died after a further bleed.…”
Section: Discussionmentioning
confidence: 99%
“…This observation agrees well with previous reports (Goulston and Coome, 1968;Valman, Parry, and Goghill, 1968;Blane and Fryers, 1970;Langman, Gastrectomy for the patient with a peptic ulcer without haemorrhage has an acceptable mortality, but when the gastrectomy is for a bleeding ulcer this figure rises to an unacceptable level, such as the 15 per cent reported by Ward-McQuaid, Pease, Smith, and Twort (1960) and the 12 per cent observed by one of us (R. T. G.) in an unpublished series of 40 gastrectomies for bleeding peptic ulcer. Vagotomy and pyloroplasty with undersewing of the bleeding point as an alternative to gastrectomy in the emergency treatment of bleeding duodenal ulcer was suggested by Smith and Farris (1958) and has received support from other observers (Dorton, 1961 ;Carruthers, Giles, Clark, and Goligher, 1967;Schiller and others, 1970;Boulos, Harris, Wyllie, and Clark, 1971;Bradley and Pollock, 1972). These workers have all reported a reduced mortality without a significant increase in re-bleeding, and our findings would tend to support this.…”
Section: Discussionmentioning
confidence: 99%
“…T h e current trend, if any, is towards more conservative operations, such as vagotomy and drainage. Carruthers, Giles, and Clark (1967), in discussing conservative surgery for bleeding peptic ulcers, had 13 cases of acute erosions in a series of I 17 patients who were treated by emergency surgery. Of these 13 patients with erosions, 4 had partial gastrectomies, 3 of which continued to bleed postoperatively, m d I died.…”
Section: Discussionmentioning
confidence: 99%